STUDI KOMPARATIF HERMENEUTIKA KONTEKSTUAL DAN QIRA’AH MUBADALAH TENTANG “DUA BANDING SATU” HARTA WARISAN (QS AL-NISA - Djama, Yusran (UIN Mataram, 2024)
This paper discusses the expression two to one listed in QS al-Nisa>' 11. This paper seeks to record the views of the two figures, namely Abdullah Saeed and Faqihuddin Abdul Kodir, which according to the author, there is a re-reading of religious texts, especially in QS al-Nisa>' 11. This paper uses qualitative research with the type of library research (literature) by referring to primary sources, namely the book Interpreting the Qur'an: Towards a Contemporary Approach and Faqihuddin Abdul Qadir's book entitled Qir?'ah mub?dalah. The results of the study show that in understanding inheritance, both of them view that